Pengaruh Model Discovery Learning terhadap Pemahaman Konsep Siswa pada Pelajaran IPA - Nishfiya Ramdoniati; Aan Nuzila Kurratul Aeni (Lembaga Yasin AlSys, 2026)
Understanding science concepts is an important ability that needs to be developed among elementary school students so that they can meaningfully understand natural phenomena, including material on changes in forms of energy. This study aims to determine the effect of the discovery learning model on fourth-grade students’ understanding of science concepts at SDN 2 Lenek Lauk, Lenek Subdistrict, East Lombok Regency. This study used a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The research population included all fourth-grade students, totaling 27 students, with the sampling technique using saturated sampling. Data were collected through observation, tests, and documentation, then analyzed using the paired sample t-test. The results of the study show an increase in students’ mean scores from 77.96 in the pretest to 90.56 in the posttest. The results of the hypothesis test showed a significance value of < 0.05 and a calculated t-value of 5.907, which was greater than the t-table value of 1.708, indicating a significant effect between the implementation of the discovery learning model and students’ understanding of science concepts. The conclusion of the study affirms that the discovery learning model has a positive effect on fourth-grade students’ understanding of science concepts on the material of changes in forms of energy at SDN 2 Lenek Lauk. The implications of this study indicate that discovery learning can be used as an alternative learning model that encourages active involvement, exploration, and more meaningful conceptual understanding in science learning in elementary schools.